Socio-cultural and Economic Dynamics of Early Marriage: A Qualitative Study in Rural Areas - Munasir; Ansori, Miswan; Choeri, Imron (Universitas Djuanda, 2025)
Despite the enactment of legal restrictions on early marriage, the issue persists, particularly in rural areas of Central Java, where rates have increased. This study's main problem is the significant knowledge gap regarding how formal age-restriction policies are mediated and often undermined by deeply ingrained social and cultural norms at the community level. While previous studies have provided a broad overview of the impacts, they often lack a nuanced, micro-level understanding of the complex tensions between policy intentions and local realities. This research, therefore, provides a focused, qualitative analysis of the socio-economic dynamics of early marriage in a specific case study of rural Jepara, Indonesia. The study’s primary objectives were to analyze the social and economic impacts of the policy, identify community-level challenges, and offer actionable recommendations. A qualitative case study design involved in-depth interviews with 30 purposively selected informants, including adolescents, parents, community leaders, and government officials. The data, collected through interviews and observations, were analyzed using thematic analysis. The findings reveal a compelling tension between the policy's aims and strong traditional norms, such as the stigma of delaying marriage. While the policy has positively influenced families to prioritize education and long-term economic welfare, social pressure has significantly hampered its effectiveness. This study's unique contribution lies in its in-depth exploration of this tension, providing a grounded basis for future policy and community interventions. The conclusion clarifies how these findings address the research objectives and offers concrete recommendations for a more holistic approach that combines legal measures with targeted, community-based support and dialogue.